Photoelectron spectromicroscopy analysis of graphene during gate-controlled photo-oxidation process. (1st December 2022) - Nagamura, Naoka; Konno, Shun; Matsumoto, Morihiro; Zhang, Wenxiong; Kotsugi, Masato; Oshima, Masaharu; Nouchi, Ryo
Abstract: The analysis of chemical reactions in two-dimensional (2D) materials is becoming increasingly important for device applications. Typically, 2D materials are in the form of small flakes; therefore, local inhomogeneities between or within the flakes should be investigated. In this study, we investigated the gate-controlled UV photo-oxidation reaction of monolayer graphene sheets using field-effect transistor structures. We performed a surface characterization of the photo-oxidized graphene micro-sheets using an original scanning photoelectron microscopy system that enables element-selective electronic and chemical state analysis with a high spatial resolution. We succeeded for the first time in experimentally revealing the progression of the photo-oxidation reaction in graphene from the edge. During the photo-oxidation process, hole doping from the adsorbed molecules occurred first. The reaction proceeded selectively to the edges of the graphene sheets. Defects were then introduced by chemical reactions with adsorbed molecules, and finally the graphene sheets decomposed and disappeared.